Effectiveness of Thoracic Ultrasonography in the Evaluation of the Severity of Pulmonary Involvement in Patients With Systemic Sclerosis - Ebru ÇAKIR EDİS,; Osman N. HATİPOĞLU,; Ömer N. PAMUK,; Renginar MUTLUCAN ERASLAN,; Meryem AKTÖZ,; Sedat Alpaslan TUNCEL, (Archives of Rheumatology, 2016)
Objectives: This study aims to investigate the effectiveness of thoracic ultrasonography (USG) in a single session in the evaluation of the severity of pulmonary involvement in systemic sclerosis. Patients and methods: A total of 48 consecutive systemic sclerosis patients (2 males, 46 females; mean age 50.8±11.9 years; range 21 to 76 years) followed-up in our center were included. A thoracic USG using a linear probe was performed for each patient to evaluate the parenchymal involvement by two pulmonary disease specialists. The number of B-lines (B-lines described USG sign of interstitial lung fibrosis) was recorded. Systolic pulmonary artery pressure was measured by means of using a phase probe to evaluate pulmonary hypertension in the same sequence. The same day, pulmonary function tests were conducted. Warrick score was calculated according high resolution computed tomography (HRCT) images which were evaluated independently from each other by a radiologist and a pulmonary disease specialist. Medsger severity scale was calculated for each patient according to the results of HRCT findings, pulmonary function test, and systolic pulmonary artery pressure. Results: The number of B-lines detected on thoracic USG was correlated with the Warrick score (r=0.89; p=0.0001) and Medsger disease scale (r=0.55; p=0.0001) and negatively correlated with diffusing capacity of carbon monoxide (r= -0.56; p=0.0001) and forced vital capacity (r= -0.46; p=0.001). When HRCT was accepted as the gold standard; the sensitivity, specificity, positive predicted value, and negative predicted value for thoracic USG were 100%, 84.2%, 90.6%, and 100%, respectively. If thoracic USG was used instead of HRCT for the evaluation of Medsger scale, the results changed in only one of the 48 patients. Conclusion: Thoracic USG showed good correlation with HRCT findings for the evaluation of pulmonary parenchymal involvement in systemic sclerosis. Therefore, USG might be a noninvasive and useful tool for the long-term follow-up of systemic sclerosis patients after initial examination with USG and HRCT.